2003
DOI: 10.1016/s1097-2765(03)00366-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Activity Is Required for SWI/SNF Function In Vivo and Is Accomplished through Two Partially Redundant Activator-Interaction Domains

Abstract: The SWI/SNF complex is required for the expression of many yeast genes. Previous studies have implicated DNA binding transcription activators in targeting SWI/SNF to UASs and promoters. To determine how activators interact with the complex and to examine the importance of these interactions, relative to other potential targeting mechanisms, for SWI/SNF function, we sought to identify and mutate the activator-interaction domains in the complex. Here we show that the N-terminal domain of Snf5 and the second quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 33 publications
4
112
0
Order By: Relevance
“…The activator-Tra1 interaction was also revealed by in vivo FRET analysis (Bhaumik et al 2004) and by in vitro interaction and functional studies in vivo (Brown et al 2001). Similarly, two subunits of the chromatin remodeler SWI/SNF interact with Gcn4 in functional assays (Prochasson et al 2003). Recent studies indicate that Rap1, a yeast factor that participates in activation of most ribosomal protein genes as well as many other genes, functionally interacts with several subunits of TFIID Papai et al 2010).…”
Section: Activator Targetsmentioning
confidence: 98%
“…The activator-Tra1 interaction was also revealed by in vivo FRET analysis (Bhaumik et al 2004) and by in vitro interaction and functional studies in vivo (Brown et al 2001). Similarly, two subunits of the chromatin remodeler SWI/SNF interact with Gcn4 in functional assays (Prochasson et al 2003). Recent studies indicate that Rap1, a yeast factor that participates in activation of most ribosomal protein genes as well as many other genes, functionally interacts with several subunits of TFIID Papai et al 2010).…”
Section: Activator Targetsmentioning
confidence: 98%
“…Recruitment likely occurs by direct interaction with transcriptional activators (Yudkovsky et al 1999). As several different activators can recruit Swi/Snf, the nature of the activator-Swi/Snf interaction is of interest; studies have shown that two or three Swi/Snf subunits can participate in recruitment (Neely et al 2002;Prochasson et al 2003;Ferreira et al 2009). Once at a promoter, the association of Swi/Snf is stabilized by the Snf2 bromodomain (Hassan et al 2001(Hassan et al , 2002, which binds acetylated histone tails (Dhalluin et al 1999); this represents an example of cooperation between Gcn5 histone acetylation and Swi/Snf and is consistent with reports that Swi/Snf association is Gcn5 dependent (Govind et al 2005;Mitra et al 2006).…”
Section: Regulation Of Transcription By Swi/snfmentioning
confidence: 99%
“…The DNase I digestion assay was carried out as previously described (Prochasson et al 2003) with the following modifications: The templates used, 147-and 183-bp, were generated by PCR from the plasmid p601 (Lowary and Widom 1998), 5Ј-end-labeled, and used as naked DNA or as reconstituted mononucleosome template in this assay. In a 30-µL reaction, 1.6 nM of labeled and cold nucleosome template were preincubated with 2.9 nM of HIR complex for 1 h at 30°C, where indicated, prior to addition of 2.1 nM SWI/SNF complex for 30 min at 30°C, and then digested by DNase I.…”
Section: Dnase I Digestion Assaymentioning
confidence: 99%
“…The SWI/ SNF complex can be recruited to specific promoters through a variety of mechanisms, one of which is through direct interaction with sequence-specific transcriptional activators. We previously showed that activator-interaction domains within the Snf5 and Swi1 subunits play a critical role in the promoter targeting of SWI/SNF, which is essential for its function in vivo (Prochasson et al 2003).Deletion analysis of SWI/SNF subunits demonstrates that they are required for maximal expression of the histone genes (Dimova et al 1999). However, mutations that eliminated HIR-mediated repression bypassed the histone gene promoter's dependence on SWI/SNF (Dimova et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation